Spatio-temporal of landslide potential in upstream areas, Bali tourism destinations: remote sensing and geographic information approach - I Wayan Diara; I Ketut Agus Wahyu Wiradharma; R Suyarto; W Wiyanti; Moh Saifulloh (Brawijaya University, 2023)
Upstream Bali has tourist destinations with beautiful natural panoramas such as mountains, forest areas, and lakes. Characteristics of the area with steep slopes, high rainfall, and altitude above 1,500 masl. The area is inseparable from the threat of disasters, such as landslides, especially in the Baturiti District. This area often experiences landslides but has not been mapped spatially. Mitigation efforts are needed to minimize the impact of landslides. This study aimed to determine the potential for landslides and their distribution in different periods, namely 2000, 2010, and 2020. The scoring method considers four parameters: rainfall, slope, soil type, and vegetation density, using ArcGIS 10.8 Apps. Parameters extracted from remote sensing data include Landsat with ETM+ and OLI sensors, rainfall from the CHIRPS satellite, and slopes from DEMNAS. Geographic Information System (GIS) data includes soil types. Another role of GIS is to quantify raster data to build a landslide potential prediction model. Baturiti Subdistrict has a low to high potential for landslides, which are administratively distributed in Candikuning, Baturiti, Antapan, Batunya, and Bangli villages. The landslide potential in the high category in 2000, 2010, and 2020 respectively, is 70.12 ha (1%), 597.05 ha (5%), and 39.12 ha (1%). Based on the findings of this study, the leading cause of landslides is high rainfall followed by reduced vegetation density. Other factors include steep slopes (>45%) and soil types of Andosol and Regosol.